EVOLUTION OF HIGH-SPEED AERODYNAMICS - Мартинюк, Яна; Чурсанова, Марина; Дрозденко, Олександра (SWorldJournal, 2026)
This paper presents a review of the development of aircraft aerodynamics from the perspective of the engineering challenges faced by designers over the past several decades. These challenges became particularly pronounced in the transonic and supersonic s